Legal Analysis of the Establishment of a Special Electoral Court as an Independent State Institution - L.M. Ricard Zeldi Putra; La Ode Muhram (Lembaga Penelitian dan Pengabdian Masyarakat, 2021)
Article 24 of the 1945 Constitution only on structure but not on institutional functions where there are still many institutions/agencies in the government that carry out judicial functions. The regulation has led to the emergence of several independent institutions to carry out judicial functions, one of which is a special election court. The research used is normative research with an approach that focuses on the theoretical approach, the statutory approach, the case approach and is described in a qualitative descriptive form. The special election judiciary as an independent institution that will be formed is again from the law that aspires to, namely an institution that is free from intervention and can carry out judicial functions and disputes over the results of the elections. This special court is under the jurisdiction of the Supreme Court and will take the form of ad hoc. Its authority is to examine and adjudicate disputes over election results.